Les "formations-impasses" en entreprise dans les pays en développement : le cas des enfants travailleurs - Magali Decrossas (Les éditions de la Maison des sciences de l'Homme, 2005)
This article aims to study opportunities of training for working children. It focuses on the only informal sector able to accumulate human capital - the "evolutive" informal sector - and looks at the types of training offered in this sector. The paper then analyzes management strategies with regard child labour force, more precisely in terms of training, and highlights the case of bonded child labour. The conclusion shows how the training received by child workers is of little help in their professional life.